PERBEDAAN KEJADIAN KONSTIPASI PADA BAYI USIA 0-6 BULAN YANG ASI EKSLUSIF DAN NON EKSLUSIF - Juni Setiawan (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2017)
Exclusive breastfeeding is the best food for babies. Breastfeeding will prevent malnutrition because breastfeeding contains the nutrients the baby needs properly, is easy to use efficiently by the baby's body and protects the baby against infection. Therefore, the immune substances contained in breastfeeding are very useful. Breastfeeding is a complex solution containing carbohydrates, fats, and proteins (Suradi, 2010). The purpose of this study was to determine the difference of constipation occurrence in infants aged 0-6 months exclusive breastfeeding and not exclusive breastfeeding in Sumberwaru Village Banyuputih District Situbondo Regency in 2016. This research was an analytical study using Fisher's Exact Tests. Population in this study were all mothers, especially mothers who have infants aged 0-6 months exclusively breastfed and not exclusive breastfeeding in Sumberwaru Village Banyuputih District Situbondo Regency in 2016 as many as 50 people, and the sample in this study as many as 50 respondents. The results of this study indicated that respondents who were given exclusive breastfeeding as much as 16 respondents 32% of 50 respondents, and not exclusive breastfeeding as many as 34 babies 68%, whereas babies who are not exclusive breastfeeding and constipation occurred as many as 34 respondents 68%. the results of the test obtained